Size of Government and Economic Growth: A Convergence Analysis of Former Soviet Union Countries from 1991 to 2018 - Juan David García González; Jose Ramos Pires Manso; Juan Milán García; Jaime de Pablo Valenciano (Amfiteatru Economic, 2024)
There are 15 independent countries that emerged (re-emerged) from the Union of Soviet Socialist Republics since its collapse in 1991. The process of independence of the Former Soviet Union (FSU) countries was followed by massive economic, political, and institutional reforms that, in most cases, sought the transition from centralised systems to market economies. This paper uses the club convergence method developed by Phillips and Sul (2007, 2009) to analyse convergence in terms of size of government and economic growth between 1991 and 2018 for 14 FSU countries: Armenia, Azerbaijan, Belarus, Estonia, Georgia, Kazakhstan, Kyrgyzstan, Lithuania, Latvia, Russia, Tajikistan, Turkmenistan, Ukraine, and Uzbekistan. The results suggest the existence of two convergence clubs in terms of size of government. In both groups, the government spending has been reduced until 2008, followed by a stabilisation process. Turkmenistan is the only non-convergent country to any club. Likewise, there are three different convergence clubs in terms of GDP per capita. The analysis of economic convergence and the size of government in the FSU countries provides valuable insight into their path to sustainability. Economic efficiency, social equity, and institutional stability are essential components that these countries must strengthen to achieve long-term sustainable development